2019
DOI: 10.1186/s12284-019-0312-z
|View full text |Cite
|
Sign up to set email alerts
|

Functional Identification of Novel Cell Death-inducing Effector Proteins from Magnaporthe oryzae

Abstract: Background Secreted effector proteins play critical roles in plant-fungal interactions. The Magnaporthe oryzae genome encodes a large number of secreted proteins. However, the function of majority of M. oryzae secreted proteins remain to be characterized. We previously identified 851 in planta-expressed M. oryzae genes encoding putative secreted proteins, and characterized five M. oryzae cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 52 publications
(80 reference statements)
0
26
0
Order By: Relevance
“…The M. oryzae genome harbors 19 proteins with the CFEM domain (Kou et al, 2017). Two CFEM-containing proteins Wang et al, 2003;Zhang et al, 2004; Billard et al, 1988;Huet and Pernollet, 1989 P. colocasiae † 15-kDa glycoprotein Elicitin ND Induces cell death and SAR in taro leaf Mishra et al, 2009 P. cryptogea † Cryptogein Elicitin ND Induces cell death, SAR and defense of tobacco against P. nicotianae Ricci et al, 1989;Galiana et al, 1997;Mikes et al, 1997;Leborgne-Castel et al, 2008;Coursol et al, 2015;Kulik et al, 2015;Ptáčková et al, 2015;Starý et al, Huet et al, 1994;Kamoun et al, 1997Kamoun et al, , 1998Kanzaki et al, 2003;Huitema et al, 2005;Du et al, 2015 (Continued) Frontiers in Genetics | www.frontiersin.org Mateos et al, 1997;Khatib et al, 2004 P. parasitica † PpNLP/NLP Pp NLP ND Induces cell death; carries a nlp20 pattern recognized by RLP23 which associates with SOBIR1 and BAK1 complex to trigger immune responses Fellbrich et al, 2002;Qutob et al, 2006;Ottmann et al, 2009;Böhm et al, Kamoun et al, 1993;Mouton-Perronnet et al, 1995;Capasso et al, 1999 PPTG_02039, PPTG_14297, PPTG_09966 MoCDIP2 and MoCDIP11 have been identified to induce cell in the non-host N. benthamiana and host rice cells Guo et al, 2019). MoCDIP2 contains a CFEM domain at the N-terminus, and a GPI-anchored site at the C-terminus, whereas MoCDIP11 contains only a CFEM domain at the N-terminus.…”
Section: Major Protein Families Of Oomycete and Fungus Apoplastic CDImentioning
confidence: 99%
See 4 more Smart Citations
“…The M. oryzae genome harbors 19 proteins with the CFEM domain (Kou et al, 2017). Two CFEM-containing proteins Wang et al, 2003;Zhang et al, 2004; Billard et al, 1988;Huet and Pernollet, 1989 P. colocasiae † 15-kDa glycoprotein Elicitin ND Induces cell death and SAR in taro leaf Mishra et al, 2009 P. cryptogea † Cryptogein Elicitin ND Induces cell death, SAR and defense of tobacco against P. nicotianae Ricci et al, 1989;Galiana et al, 1997;Mikes et al, 1997;Leborgne-Castel et al, 2008;Coursol et al, 2015;Kulik et al, 2015;Ptáčková et al, 2015;Starý et al, Huet et al, 1994;Kamoun et al, 1997Kamoun et al, , 1998Kanzaki et al, 2003;Huitema et al, 2005;Du et al, 2015 (Continued) Frontiers in Genetics | www.frontiersin.org Mateos et al, 1997;Khatib et al, 2004 P. parasitica † PpNLP/NLP Pp NLP ND Induces cell death; carries a nlp20 pattern recognized by RLP23 which associates with SOBIR1 and BAK1 complex to trigger immune responses Fellbrich et al, 2002;Qutob et al, 2006;Ottmann et al, 2009;Böhm et al, Kamoun et al, 1993;Mouton-Perronnet et al, 1995;Capasso et al, 1999 PPTG_02039, PPTG_14297, PPTG_09966 MoCDIP2 and MoCDIP11 have been identified to induce cell in the non-host N. benthamiana and host rice cells Guo et al, 2019). MoCDIP2 contains a CFEM domain at the N-terminus, and a GPI-anchored site at the C-terminus, whereas MoCDIP11 contains only a CFEM domain at the N-terminus.…”
Section: Major Protein Families Of Oomycete and Fungus Apoplastic CDImentioning
confidence: 99%
“…Targeted deletion of the genes encoding these proteins did not impair the virulence of pathogens ( Table 2). One possibility why these apoplastic CDIPs were dispensable for virulence could be due to the functional redundancy with other apoplastic effectors (Yoshino et al, 2012;Guo et al, 2019).…”
Section: Apoplastic Cdips Contribute To Pathogen Virulencementioning
confidence: 99%
See 3 more Smart Citations